Repeated Ingestion of an Unusual Foreign Body together with the Insertion of a Foreign body in the Bladder - Mohammad Hossein Taziki; Mohammad Reza Yousefi; Hamid Reza Tajari (Golestan University of Medical Sciences, 2018)
Background and objectives: Pieces of food or other material maybe accidentally ingested and entrapped in the alimentary tract. In rare cases, this material may be ingested by the patient purposely, and leads to some problems. In addition to ingestion of foreign body, they may perform some unusual behavior such as the insertion of wire into the bladder. Methods: The patient is a 37-year-old man that referred to hospital with dysphasia and odynophagia following the ingestion of a big peach nucleus. After diagnostic interventions, he was investigated by Esophagoscopy.  After that, he said that he ingested a big nail cutter. X-Ray examination showed that this nail cutter was in stool. Results: Immediately he said that he chewed a Fluor cent   lump and ingested some of it. In the past, he inserted an electrical wire to the bladder by himself after sometimes it is extracted frame the bladder by urologist. Finally, the patient referred to psychiatric ward for continuing the treatment. Conclusion: When patient ingest foreign body unduly, evaluation of psychologic dimensions is mandatory, and for the treatment team a psychiatrist is necessary.